Komunikasi Interpersonal Orang Tua dalam Pencegahan Pernikahan Dini Terhadap Anak Usia Remaja di Kecamatan Medan Sunggal - Safira, Arina; Deni, Indira Fatra (Asosiasi Ide Bahasa Kepri, 2024)
Preventing early marriage poses significant challenges for parents in Medan Sunggal, exacerbated by social influences and peer pressure. Effective communication emerges as a crucial strategy in navigating these complexities, bridging generational gaps and addressing the impact of social media on adolescents. This study examines the experiences of parents in Medan Sunggal through qualitative interviews with individuals such as Ibu SR and Pak RD. Their insights highlight the effective use of open dialogue and real-life examples to educate children about the risks of early marriage. Parental efforts in fostering open communication have proven instrumental in helping adolescents understand the importance of delaying marriage until they are emotionally and financially prepared. By discussing future plans and illustrating real-world consequences, parents strengthen familial bonds and empower children to make informed decisions amidst societal pressures.